Menakar Kualitas Demokrasi dalam Pelaksanaan Pilkada 2024 di Kecamatan Cibitung Kabupaten Bekasi - Gunawan, Shafaa Qathrunnada; Muslim, Jaliludin (UIN Sunan Gunung Djati Bandung, 2025)
A quality democracy is reflected in the implementation of regional head elections (Pilkada) that are transparent, participatory, and accountable. This study aims to examine the quality of democracy in the implementation of the 2024 regional elections in Cibitung Sub-district, Bekasi Regency, with a focus on the level of community participation, the impact of money politics, and the transparency and accountability of organisers. Using a qualitative method with in-depth interviews, this research involved six informants who were purposively selected. The results show that voter participation is still constrained by administrative issues and population mobility, while the practice of money politics remains a major challenge that undermines the integrity of democracy. On the other hand, the organisation of the elections was considered quite transparent, despite concerns about potential fraud. Social media is the main source of political information, but it has not been matched by adequate political literacy. In conclusion, the quality of democracy in Cibitung Sub-district requires improvement through strengthening supervision, intensive political education, and reform of the electoral administration system to support more inclusive participation